2012
DOI: 10.1007/s00011-012-0467-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical observation of immunity in patients with secondary infection from severe acute pancreatitis

Abstract: An early excessive immune response followed by a subsequent immune deficiency is closely related to secondary SAP infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…The shift in microbial community structure was reported to induce the expression of TNFα and IL-6 expression in intestine [8] and then exaggerated the intestinal barrier injury in IBD. Acute pancreatitis is characterized by excessive release of inflammatory cytokines in both system and intestine [9]. …”
Section: Introductionmentioning
confidence: 99%
“…The shift in microbial community structure was reported to induce the expression of TNFα and IL-6 expression in intestine [8] and then exaggerated the intestinal barrier injury in IBD. Acute pancreatitis is characterized by excessive release of inflammatory cytokines in both system and intestine [9]. …”
Section: Introductionmentioning
confidence: 99%
“…Despite persistent efforts and rapid advances in early anti-inflammatory and organ-supportive treatment measures, the mortality rate remains high, and infectious complications are the dominant cause of late mortality [3,4]. Early immune dysfunction followed by immunosuppression is associated with infectious complications [5]. Immunosuppression occurs in the early phase of AP, leading to susceptibility of the host to infectious complications and then to systemic sepsis in the late stage [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Shen et al [8] reported that the levels of TNF-α and IL-6 in a MODS group of SAP patients differed from those of a non-MODS group, with higher levels on days 3 and 7, and lower levels on day 14 in the early stage. Shen and Cui [9] reported that the cytokine levels in an infected group differed from those in a noninfected group, with a rise in TNF-α and IL-6 through the first 2 weeks, but dropping at 1 month. Moreover, IL-10 and IL-4 increased initially, but then dropped over the next 3 weeks in the late stage.…”
Section: Discussionmentioning
confidence: 97%
“…Some researchers suggest that the excessive inflammatory immune response to SAP mediates pathological damage and that immune dysregulation plays an important role in infection and organ dysfunction [8,9]. However, few studies have investigated the relationship between the severity of the event and immune dysregulation in the course of SAP.…”
Section: Introductionmentioning
confidence: 97%